Quantifying the dispersal potential of seagrass vegetative fragments: A comparison of multiple subtropical species. (5th February 2016) - Weatherall, E.J.; Jackson, E.L.; Hendry, R.A.; Campbell, M.L.
Abstract: Seagrass meadows are threatened by anthropogenic and natural disturbances on both a local and global scale. Understanding the potential for seagrasses to disperse, connecting populations separated by unsuitable habitat is important to assess the resilience of regional populations. This study investigated the relative dispersal potential of vegetative fragments of seagrass from five subtropical species ( Zostera muelleri, Halodule uninervis, Halophila ovalis, Halophila spinulosa, Halophila decipiens ). Five questions were examined: 1) do vegetative fragments of different species settle at different velocities; 2) does a species morphometric variables influence settling velocities; 3) is a species settling velocity related to the species local distribution; 4) does temperature stress affect settling velocity; and 5) what is the composition and potential viability of seagrass fragments floating in the bay. A proportional distribution index for each species was determined using data from a habitat prediction model. It was found that H. spinulosa settled significantly faster than the remaining species and Z. muelleri settled the slowest. Variables influencing settling velocity included rhizome length, weight and surface area. In both Z. muelleri and H. ovalis settling velocities were significantly greater at higher temperatures (although there was no significant difference between approximately 5 and 10 °C above ambient temperature). H. uninervis was not significantly influenced by temperature. There was a significant negative correlation between species settling velocities and their distribution.